‘Cherry Tart’ – A Dwarf Red Lance-Leaved Caladium Variety - Zhanao Deng (EDIS)
This 5-page fact sheet introduces a new lance-leafed caladium variety that was released in April 2011. It has bright red color, slightly undulate leaf margins, and a broadly cordate leaf shape. Written by Zhanao Deng and published by the UF Department of Environmental Horticulture, August 2011.